Diagnosis of the Science, Innovation, Technology and Environment System of Physical Culture and Sports/Diagnóstico del Sistema de Ciencia, Innovación, Tecnología y Medio Ambiente de Cultura Física y Deporte - Osvaldo Vento Montiller; Melix Ilisástigui Avilés; Mayda Losada Robaina (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: Cuba, immersed in a tenacious struggle for its identity and development since the beginning of the Revolution, set out to develop its scientific-technical potential. Today it can be talked about science at the National Institute of Sports, Physical Education and Recreation. This organization has a qualified scientific human potential, which directs its research in this branch and the satisfactory results that translate into medals are inescapable evidence. The established policy on Science, which establishes the regulations and legal bases for the application of Science, Technology, Innovation and the Environment, takes into account the state of the processes that comprise it. Objective : To determine the causes and barriers that limit the functioning of the System of Science and Technological Innovation of Physical Culture and Sports (SCITMA of CFD) in Cuba. Materials and methods: A group of methods and techniques were applied for this purpose (documentary analysis, Brainstorming technique, SWOT matrix, CAP survey, Ishikawa Diagram). Results: These applied techniques revealed the causes and barriers that limit the functioning of the System of Science, Technology, Innovation and Environment of Physical Culture and Sports in Cuba, a result that allowed rationally anticipating and ordering the changes and actions required for this purpose. Conclusions: The route for change was presented based on strategies with short and medium term goals, in which the minimum conditions for its implementation are established.